A novel method of ultrasound-guided positive staining using indocyanine green fluorescence in laparoscopic anatomical liver resection of segments VII and VIII - Jiang, Zedong; Zhou, Bo; Zheng, Xiang; Li, Guogang; Gao, Zhenzhen; Tian, Yang; Shao, Chunlong; Xu, Shaoyan; Yan, Sheng (Frontiers in Oncology, 2023)
Background Recently, in many Asian centers, laparoscopic anatomical liver resection (LALR) using the indocyanine green (ICG) fluorescence imaging technique has been increasingly applied in resecting hepatocellular carcinoma, even in colorectal liver metastases. However, LALR techniques have not been fully standardized, especially in right superior segments. Due to the anatomical position, prevailing positive staining using a PTCD (percutaneous transhepatic cholangial drainage) needle was superior to negative staining in right superior segments hepatectomy, while it was difficult to manipulate. Herein, we design a novel method of ICG-positive staining for LALR of right superior segments. Methods Between April 2021 and October 2022, we retrospectively studied patients in our institute who underwent LALR of right superior segments using a novel method of ICG-positive staining, which comprised a customized puncture needle and an adaptor. Compared to the PTCD needle, the customized needle was not limited by the abdominal wall and could be punctured from the liver dorsal surface, which was more flexible to manipulate. The adapter was attached to the guide hole of the laparoscopic ultrasound (LUS) probe to ensure the precise puncture path of the needle. Guided by preoperative three-dimensional (3D) simulation and intraoperative laparoscopic ultrasound imaging, we punctured the transhepatic needle into the target portal vein through the adaptor and then slowly injected 5-10 ml of 0.025 mg/ml ICG solution into the vessel. LALR can be guided by the demarcation line under fluorescence imaging after injection. Demographic, procedural and postoperative data were collected and analyzed. Results In this study, 21 patients underwent LALR of the right superior segments with ICG fluorescence-positive staining, and the procedures had a success rate of 71.4%. The average staining time was 13.0 ± 6.4 min, the operative time was 230.4 ± 71.7 min, R0 resection was 100%, the postoperative hospital stay was 7.1 ± 2.4 days, and no severe puncture complications occurred. Conclusions The novel customized puncture needle approach seems to be feasible and safe for ICG-positive staining in LALR of right superior segments, with a high success rate and a short staining time.